Problematika Kepastian Hukum Terhadap Penerapan Restorative Justice Dalam Penanganan Perkara Tindak Korupsi Dana Desa - Suheflihusnaini Ashady; Aryadi Almau Dudy (Unizar Law Review, 2023)
The implementation of regional authorities and the allocation of village funds that should be used for welfare and development at the village level have instead become new grounds for corruption for some elements. Law enforcement that is able to provide a deterrent effect on perpetrators is very important so that the idea and application of restorative justice to perpetrators of corruption in village funds needs to be studied further in terms of how the limitations of the application of restorative justice by law enforcement officials in a crime and whether the application of restorative justice against acts of corruption in village funds to fulfill the principle of legal certainty. This research is a normative research with a statutory approach (the statute approach) and a conceptual approach (conceptual approach). The results of the study show that law enforcement officials in implementing restorative justice for a crime must pay attention to the specified conditions, for corruption crimes cannot be applied to restorative justice based on the Head of Police Regulation Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice and the Prosecutor's Office Regulations of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice; Next, the application of law must not ignore the principle of legal certainty. Legal certainty also means the clarity of norms that become a reference for behavior, these norms contain consistency, both internally in the law and horizontal consistency with others or vertical consistency with higher laws and regulations. The application of restorative justice to criminal acts of corruption (including corruption in village funds) has violated the principle of legal certainty as well as ignoring the value of justice and the usefulness of law, so its application must be reviewed.